2013
DOI: 10.1163/15685411-00002704
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and damage potential of five species of plant-parasitic nematodes on plantain (Musa spp., AAB genome) cv. Agbagba

Abstract: The pathogenicity of five plant-parasitic nematode species, Radopholus similis, Pratylenchus coffeae, Helicotylenchus multicinctus, Hoplolaimus pararobustus and Meloidogyne spp., commonly recorded from banana and plantain in West and Central Africa, was assessed on plantain (Musa spp., AAB genome) cv. Agbagba in Nigeria. The pest status of H. pararobustus was demonstrated for the first time in addition to H. multicinctus, while the importance of P. coffeae and R. similis was further confirmed. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
9
2
Order By: Relevance
“…and the increases in production achieved with the application of nematicides indicated that their parasitism reduces growth, development, and production. These results are in accordance with observations by McSorley and Parrado (1986), Gowen and Quénéhervé (1990), Chau et al (1997), Barekye et al (1998Barekye et al ( , 2000, Gowen (2000), Guzmán-Piedrahita (2011a), Coyne et al (2013), and Salguero et al (2016), who reported that H. multicinctus and H. dihystera damaged the banana root system and reduced yield between 19% (Speijer and Fogain, 1999) and 34% (Reddy, 1994). Additionally, Sijmons et al (1994) indicated that the induction and maintenance of feeding sites of Helicotylenchus spp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…and the increases in production achieved with the application of nematicides indicated that their parasitism reduces growth, development, and production. These results are in accordance with observations by McSorley and Parrado (1986), Gowen and Quénéhervé (1990), Chau et al (1997), Barekye et al (1998Barekye et al ( , 2000, Gowen (2000), Guzmán-Piedrahita (2011a), Coyne et al (2013), and Salguero et al (2016), who reported that H. multicinctus and H. dihystera damaged the banana root system and reduced yield between 19% (Speijer and Fogain, 1999) and 34% (Reddy, 1994). Additionally, Sijmons et al (1994) indicated that the induction and maintenance of feeding sites of Helicotylenchus spp.…”
Section: Discussionsupporting
confidence: 91%
“…causes physiological changes in the structure of cells. In the case of R. similis, it is well supported that it reduced the yield in banana (Gowen and Quénéhervé, 1990;Gowen, 1993Gowen, , 1995Araya, 1995Araya, , 2004Guzmán-Piedrahita, 2011b;Roderick et al, 2012;Coyne et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…The combination of nematode species present varies with locality with mixtures of P. coffeae , H. multicinctus , R. similis and Meloidogyne spp. often occurring in West African soils 23 .…”
mentioning
confidence: 99%
“…Infestations of complexes of species are prevalent and the combination of nematode species present in banana plantations varies with the locality (Coyne et al. ).…”
Section: Nematode Resistant Bananasmentioning
confidence: 99%
“…differs in modifying plant cells into a feeding site at one locale (Gowen et al 2005). Infestations of complexes of species are prevalent and the combination of nematode species present in banana plantations varies with the locality (Coyne et al 2013).…”
Section: Nematode Resistant Bananasmentioning
confidence: 99%